Content guidance for mobile phones short message service (SMS)-based antiretroviral therapy adherence and appointment reminders: a review of the literature. Issue 5 (4th May 2019) - Kerrigan, Andrew; Kaonga, Nadi N.; Tang, Alice M.; Jordan, Michael R.; Hong, Steven Y.
ABSTRACT: Mobile phones are increasingly being used to support health activities, including the care and management of people living with HIV/AIDS. Short message service (SMS) has been explored as a means to optimize and support behaviour change. However, there is minimal guidance on messaging content development. The purpose of this review was to inform the content of SMS messages for mobile health (mHealth) initiatives designed to support anti-retroviral therapy adherence and clinic appointment keeping in resource-limited settings. PubMed, OvidMedline, Google Scholar, K4Health's mHealth Evidence database, the mHealth Working Group project resource, and Health COMpass were searched. A request to online communities for recommendations on message content was also made. 1010 unique sources were identified, of which 51 were included. The information was organized into three categories: pre-message development, message development, and security and privacy. Fifteen of the publications explicitly provided their message content. Important lessons when developing the content of SMS were: (1) conducting formative research; (2) grounding content in behaviour change theory; and (3) reviewing proposed content with experts. Best practices exist for developing message content for behaviour change. Efforts should be continued to apply lessons learned from the existing literature to inform mHealth initiatives supporting HIV/AIDS care and treatment.